Historical aspects of the emergence of mediation as a form of protection of intellectual property rights - Turlai, Oleh (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
According to Art. 1 of the Constitution of Ukraine is a social, democratic and legal state. Its development, in accordance with constitutional provisions, is impossible without effective means of protecting human rights and freedoms, including rights to intellectual property objects. It is worth noting that in modern conditions, intellectual property is developing rapidly, its objects are becoming more widespread, so it needs proper protection. The reason for the violation of intellectual property rights is the nature of the objects themselves, which makes it possible to easily and quickly reproduce and distribute them. In world practice, various forms of protection of these rights are used. But protecting them in court, as a rule, requires a lot of time, money and effort. Therefore, mediation is increasingly used as a form of protection of intellectual property rights. An important condition for the integration of our country into the European Union is the creation of a legal framework that would meet international standards, in particular in the field of intellectual property. It is important to adopt the positive experience of foreign countries in the field of legal regulation and functioning of alternative methods of dispute resolution. It should be noted that mediation in Ukraine is just beginning its development, however, on the basis of international standards and experience, we can analyze which aspects of legal regulation need to be improved, in particular for the protection of intellectual property. The use of mediation in the field of intellectual property in Ukraine would contribute to the improvement of the efficiency of dispute resolution, would improve the legal mechanisms for the protection of rights and legitimate interests, and would harmonize the current national legislation with international standards in this area. The purpose of this article’s research is the issue of using mediation to resolve conflicts and protect rights to intellectual property objects.